Memorializing the Holocaust in Israel: Diasporic Encounters - Habib, Jasmin (Anthropologica, 2022)
In this paper, I explore interpretations of Israeli museum representations of the Holocaust that prevail among diasporic Jews. I address such questions as how the Holocaust, an event that so marks Jewish contemporary history and identity, is represented in a Jewish state. To what does the movement from the sites of the Holocaust in Europe to the site of its memorialization in Israel gesture? What do diasporic Jews tell us of their visits to these sites of memorialization? I also address the significance of shifting the sites of memorialization from their geographical and historical sites. The perspective on public history used in this paper is concerned with the orientation and set of conceptual balancing acts adopted and applied when reading, interpreting or experiencing forms of public history. It is also focussed on diasporic identifications with a nationalist public and state history. Its reflexive orientation suggests that particularistic and universalistic (or cosmopolitan) histories and interpretations of the Holocaust are possible and even reconcilable.